GIS-material for the archaeological project: Settlement remains at Nybygget - Offerby and others - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the arcaheological report:
Due to reconstruction of the electric main system in the Offerby-Ervasteby area, Motala municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a preliminary investigation, since the trenching was conducted nearby a known archaeological site and possible settlement sites. Four areas (objects) were selected for the antiquarian inspection. In two of them trial trenches were excavated. The other two were affected to such a small extent that no archaeological measures needed to be taken. Within Object II (site RAÄ 176:1, Motala parish) settlement remains were discovered, probably from a later chronological phase than the Stone Age remains of RAÄ 176. The remains were excavated. No archaeological remains were found within Object IV.

Purpose:

The information in the abstract is translated from the archaeological report:
The purpose of the preliminary investigation was to determine whether any archaeological remains could be affected by the planned earthworks and, if so, to avoid them if possible. If alternative locations for the trenching could not be found, the remains were to be excavated.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför ombyggnad av ledningsnät i området Offerby-Ervasteby, Motala kommun har UV Öst genomfört arkeologisk förundersökning i form av antikvarisk kontroll då de planerade arbetena skedde i anslutning till fornlämning och lämpliga boplatslägen. Fyra objekt valdes ursprungligen för antikvarisk kontroll. Av dessa blev bara två föremål för sökschaktsgrävning, då ingreppen i de resterande två bedömdes som så små att arkeologisk åtgärd ej var nödvändig.
Inom Objekt II (Motala RAÄ 176:1) påträffades boplatslämningar, vilka troligen härrör från en yngre förhistorisk fas än stenålderslämningarna vid RAÄ 176. De påträffade lämningarna undersöktes. Inom Objekt IV påträffades ej fornlämning.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var dels att utreda om fast fornlämning berördes av de planerade arbetena, dels att i möjligaste mån undvika ingrepp i dem. Om alternativa sträckningar inte kunde hittas genomfördes undersökningar av de påträffade lämningar för att möjliggöra fortsatta jordkabelnedgrävningar.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Boplatslämningar vid Nybygget - Offerby m.fl.
Keywords: Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi